14. An abnormal transduction of the chromatic stimuli from the outer to the inner retinal layers may contribute to the mechanism of photophobia in migraine. Issue 4 (April 2016) - Coppola, G.; Corso, L.; Di Renzo, A.; Fadda, A.; Martelli, F.; Di Lorenzo, C.; Parisi, V.; Schoenen, J.; Falsini, B.; Pierelli, F.
Abstract : Recent experimental evidences point out a possible involvement of retina in hypersensitivity of migraine patients to light stimuli. Our aim was to investigate the short-wavelength-sensitive and the medium/long-wavelength-sensitive cone photoreceptors of the visual pathways in migraine without aura (MO) patients between attacks and in healthy volunteers (HV) by using yellow-blue (Y-B) or red-blue (R-B) visual flicker stimuli. Square-wave focal electroretinograms (FERGs) were recorded in 22 MO patients and 20 HV. Fourier analysis allowed extracting from the FERG data the fundamental (1F) and the second harmonic (2F) components (amplitude and phase) that are related respectively to outer and inner retinal activity. Usual headache severity and photophobia during migraine were scored on a 0 to 10 visual analogue scale. When compared to HV, MO patients had an advanced 1F phase but normal amplitude in all blocks of Y-B FERG. Self-rated intensity of ictal photophobia positively correlated with attack frequency, headache severity, 1F Y-B phase, 1F R-B phase, 2F Y-B amplitude, habituation slope, and 2F R-B phase. These results suggest that an abnormal signal transduction from the outer to the inner retinal layers could contribute to the mechanisms by which light causes pain or discomfort during the migraine headache.